2023
DOI: 10.1093/cei/uxad024
|View full text |Cite
|
Sign up to set email alerts
|

Features of BAFF and APRIL receptors on circulating B cells in antineutrophil cytoplasmic antibody-associated vasculitis

Abstract: To investigate the features of circulating B cells, their expressing receptors, serum levels of B-cell activation factor of the TNF family (BAFF), and a proliferation-inducing ligand (APRIL) in antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Blood samples from 24 patients with active AAV (a-AAV), 13 with inactive AAV (i-AAV), and 19 healthy controls (HC) were included in this study. The proportion of B cells and their expressing BAFF receptor (BAFF-R), transmembrane activator and calcium modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It has been shown that even in antineutrophil cytoplasmic antibody-associated vasculitis (AAV) remission, elevated expression of TACI in CD19+ cells, immature B cells, and the proportion of plasmablast (PB)/plasma cell (PC) is accompanied by persistently high levels of BAFF and APRIL in serum (11). Persistent abnormalities in BAFF/APRIL signaling may lead to disease recurrence (12). Telitacicept is a novel fully human TACI-Fc recombinant fusion protein targeting B lymphocyte stimulators.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that even in antineutrophil cytoplasmic antibody-associated vasculitis (AAV) remission, elevated expression of TACI in CD19+ cells, immature B cells, and the proportion of plasmablast (PB)/plasma cell (PC) is accompanied by persistently high levels of BAFF and APRIL in serum (11). Persistent abnormalities in BAFF/APRIL signaling may lead to disease recurrence (12). Telitacicept is a novel fully human TACI-Fc recombinant fusion protein targeting B lymphocyte stimulators.…”
Section: Introductionmentioning
confidence: 99%